The scantness of the effect of corporate governance mechanisms on executive directors’ remuneration in small listed companies: evidence from Malaysia - Nyambia, Husna Siraji; Hamdan, Hamdino (IIUM Press, 2018)
This study extensively aims to investigate the effects of different aspects of corporate governance (CG) mechanism, including board size, executive directors’ shareholdings, Chief Executive Officer (CEO) duality, a family member as the CEO and/or chairperson of the board, independent directors in remuneration committee and number of board meeting, on executive directors’ remuneration in small firms listed on Bursa Malaysia (BM). The sample of this study consists of 173 bottom-listed companies from BM in Year 2010. The Year 2010 was chosen because the disclosure of remuneration committee activities and directors’ pay structure is required under the revised Malaysia Code of Corporate Governance, 2007. Furthermore, the period selected is after the global economic crisis (2008), which may have an effect on the remuneration structure in small firms. The ordinary least squares regression was used to estimate the relationship between remuneration as dependent variable and other independent variables. A finding from this study reveals that there is a significant positive relationship between executive ownership and executive remuneration, and between board size and executive remuneration. The results provide evidence that the family members manipulate power and control remuneration in small firms. This indicates that the independent directors are not truly independent to monitor and control the firm activities, including minimizing the excessive remuneration. This study examines how the corporate governance (CG) affects remuneration among 173 small firms in Malaysia based on market capitalization, for one year, 2010. Hence, the results may not be generalizable to other periods or types of the companies. This shows the possibility of the absence of some additional variables in the research model and hence a limitation to the findings of the study. Although the study is being parsimonious in the choice of relevant variables, prior literature serves the guide in the selection of the used variables. This therefore gives room for future research using the potential omitted variables. Furthermore, the study focuses on total remuneration, such as fees, salaries, bonuses and benefits in kind, which makes aggregate directors’ remuneration. However, this study did not consider the remuneration related to stock options. Finally, this study only uses secondary data; hence, it could be interesting to use other instruments to collect data like a questionnaire to add more weight to the research. This study only uses one-year data; therefore, impact of changes between years cannot be analysed. Results of the study provide evidence that the family members manipulate power and control remuneration in small firms. They reduce the effectiveness of non-executive directors because most of them are appointed by a family member and not socially responsible to their stakeholders.